Granular parakeratosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
Granular parakeratosis (PG) was described for the first time in 1991 by Northcutt et Al. (3) in the adult in the axillary region: the presence of compact parakeratosis with persistence of the stratum granulosum and retention of keratohyalin granules in keratinocytes of the stratum corneum is characteristic of GP. Subsequently, GP has been described in children (2, 6) in the diaper area and then in the adult in other locations, almost always in the folds. GP has a variable duration, usually short especially in the child, but sometimes it persists for more than 20 years (5). The disease is therefore characterized by the location to the folds from a clinical point of view and by the typical histologic picture. However, the latter can be found in numerous other dermatological conditions (4) and has been described also before 1991: in these cases we talk about incidental GP. The etiology of the disease has been widely discussed; certainly there are important predisposing constitutional factors given its rarity. Among the factors that favor the appearance of GP hot and sweating seem particularly important: some cases (5) regress in winter to recur in summer; there are cases of GP that affect only the ostia of the sweat glands (7); also the onset below the disposable diaper is a factor that speaks in favor of the role played by increased temperature and humidity. The increased temperature and humidity occurring at the level of the folds also explains the more frequent localization and / or the greater evidence here of some skin disorders associated with epidermal hyperplasia such as seborrheic warts, pemphigus vegetans and epidermal nevi. According to some Authors in children is important the excessive use of products for the hygiene, the cessation of which would result in rapid healing (1); we cannot confirm the importance of these factors in our cases that improved with the programmed withdrawal of the plastic disposable diaper.